Titanium alloy low-adhesion super-hydrophobic microstructure provided with concave circular truncated cones and blind holes and preparation method of titanium alloy low-adhesion super-hydrophobic microstructure

By designing the microstructure of concave round table and blind hole period arrangement and combining femtosecond laser etching and chemical fluorination treatment, the corrosion resistance and wear resistance of the titanium alloy surface in extreme environments is solved, and the superhydrophobic surface of titanium alloy is realized The low adhesion characteristics and efficient preparation are suitable for medical devices and aerospace fields.

CN119194454APending Publication Date: 2024-12-27HEBEI UNIV OF SCI & TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411345321.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing superhydrophobic surface structure of titanium alloys lacks in retention of air and reducing contact area, and the processing process is complicated, making it difficult to maintain good corrosion resistance and wear resistance in extreme environments.

Method used

Microstructures with concave round table and blind hole period arrangement were designed, and numerical equations were derived based on the Cassie-Baxter infiltration model. Superhydrophobic microstructures of titanium alloy with low adhesion characteristics were prepared by femtosecond laser etching and chemical fluorination treatment.

Benefits of technology

It realizes the superhydrophobic function of the surface of titanium alloy, reduces the adhesion characteristics, provides new design methods and low-cost preparation methods, and is suitable for medical devices and aerospace and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119194454A_ABST
    Figure CN119194454A_ABST
Patent Text Reader

Abstract

The invention discloses a titanium alloy low-adhesion super-hydrophobic microstructure provided with concave circular truncated cones and blind holes and a preparation method of the titanium alloy low-adhesion super-hydrophobic microstructure. The super-hydrophobic microstructure is composed of concave circular truncated cones and blind holes which are periodically arranged, and the micron-sized structure of the super-hydrophobic microstructure can effectively store air and form an air film layer, so that the contact area between liquid drops and the super-hydrophobic microstructure is reduced, and the super-hydrophobic function is achieved. According to the super-hydrophobic microstructure design method, a numerical equation between super-hydrophobic microstructure features and a super-hydrophobic function, namely a contact angle, is deduced and established based on a Cassie-Baxter infiltration model of a super-hydrophobic theory, corresponding microstructure feature parameters when the contact angle is larger than 150 degrees are determined, and super-hydrophobic microstructure design is completed. The preparation method of the super-hydrophobic microstructure comprises the steps that a titanium alloy material is selected and polished to 0.4-0.8 micron, femtosecond laser etching is conducted on the polished titanium alloy surface, and the microstructure with the concave circular truncated cones and the blind holes arranged periodically is prepared; in order to eliminate the high adhesion characteristic of the titanium alloy super-hydrophobic microstructure, the titanium alloy super-hydrophobic microstructure is subjected to chemical fluorination treatment and constant-temperature drying, and the titanium alloy super-hydrophobic microstructure with the low adhesion characteristic is prepared. A novel design method and a low-cost preparation approach are provided for the low-adhesion titanium alloy super-hydrophobic surface, and the low-adhesion titanium alloy super-hydrophobic surface can be widely applied to the fields of medical instruments, aerospace ice suppression and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of design and preparation of super-hydrophobic microstructures on titanium alloy surfaces, and in particular relates to a low-adhesion super-hydrophobic microstructure with periodic arrangement of concave truncated cones and blind holes and a preparation method based on femtosecond laser and chemical fluorination. Background Art

[0002] Titanium alloys are widely used in aerospace (such as turbine blades), medical devices (such as bone implants), and marine equipment (such as housings) due to their high strength, low density, corrosion resistance, and excellent biocompatibility. With the continuous advancement of surface modification technology, its scope of application has further expanded. However, the surface chemical properties of traditional titanium alloys are active, and they exhibit poor corrosion and wear resistance in extreme application environments, such as high temperature, strong acid, strong alkali, and high wear, which limits their service life and application range. By giving titanium alloys superhydrophobic properties through surface modification technology, their blood compatibility, antibacterial, drag reduction, ice suppression, and anti-corrosion properties can be significantly improved. Therefore, the design and preparation of low-adhesion superhydrophobic microstructures of titanium alloys have important application value and practical significance.

[0003] A superhydrophobic surface refers to a material surface with a water droplet contact angle greater than 150° and a rolling angle less than 10°. It has important application value in the fields of self-cleaning, corrosion protection, and frost suppression. The contact angle of a droplet on a solid surface is an important indicator for measuring wetting properties. The contact angle is the result of the surface tension balance between the three interfaces of solid, liquid, and gas. When the tension is balanced, the total energy of the system tends to the lowest, and the droplet on the solid surface is in a stable state. The droplet is incompletely infiltrated on the surface of a rough structure. The Cassie-Baxter wetting model believes that the contact surface is composed of three parts: the droplet, the micro-topography of the solid surface, and the air retained inside the micro-topography. Based on this, the Cassie-Baxter equation cos θ T = f sl ( f r cos θ c +1)-1, where θ T is the contact angle, θ c is the intrinsic contact angle, f s1 is the ratio of the actual wetted solid area of ​​the droplet to the apparent geometric contact area. f rIt represents the roughness coefficient, that is, the degree of non-smoothness of the surface. The reason why super-hydrophobic surfaces have super-hydrophobic wetting properties is mainly because the surface micro-topography can retain air, forming a large degree of Cassie-Baxter wetting state that allows the air-liquid interface to maintain, making the surface present a large contact angle. Micro-topography is a key factor affecting the high contact angle of water droplets on the surface of the material. Therefore, the preparation of super-hydrophobic surfaces mainly involves modifying low-surface-energy substances on rough surfaces with micro-topography, or constructing micro-topography on the surface of low-surface-energy materials. With the continuous exploration of surface modification technology, femtosecond laser processing technology has been widely used in the processing of surface micro-topography due to its high precision, contact-free and controllable features.

[0004] Based on the principle of super-hydrophobic surface design and preparation, research on super-hydrophobic surface design has been carried out. Taking the micro-morphological structure of the pitcher plant slip zone that can exhibit super-hydrophobic properties as a bionic prototype, a super-hydrophobic surface was designed and prepared using 3D printing technology and high-voltage electrostatic adsorption technology. The test results show that the water droplet contact angle of the prepared super-hydrophobic surface is 152.6°, indicating that it has good super-hydrophobic function (authorized invention patent, patent number ZL 202010458218.7; academic paper, Bioinspired, Biomimetic and Nanobiomaterials, 2022, 11(1): 1-7). Therefore, the patent applicant has the basic conditions for the design and preparation of super-hydrophobic surfaces.

[0005] Invention patent 202211565535.4 discloses a method for improving the superhydrophobicity of nickel-titanium alloy by laser composite processing. The surface of the nickel-titanium alloy sample is textured in turn by femtosecond laser and nanosecond laser to form a multi-level nested mesh micro-nano composite structure, thereby effectively increasing the surface roughness of the nickel-titanium alloy sample. Through further chemical modification, a nickel-titanium alloy superhydrophobic surface with excellent superhydrophobic properties and corrosion resistance is obtained. However, the micro-morphological structure involved in this patent cannot retain air well and reduce adhesion, and the processing of the multi-level nested mesh micro-nano composite structure requires multiple laser processing, and the processing process is more complicated than that of this patent. Invention patent 202311557986.8 discloses a method for preparing a super-hydrophobic surface of titanium alloy by laser nitriding and texturing, and its application. Under vacuum conditions, the titanium alloy sample is pre-scanned and processed; and under a nitrogen environment, the pre-scanned surface is simultaneously laser nitrided and texturized to achieve the preparation of a super-hydrophobic TiN periodic micro-groove coating on the titanium alloy surface. This method not only gives the titanium alloy good super-hydrophobic properties, but also improves the anti-icing properties of the titanium alloy surface. However, the micro-morphological structure involved is lacking in the ability to retain air and form an air film layer, and the processing requires both air and nitrogen environments, making the operation more complicated.

[0006] In summary, in the field of design and preparation of super-hydrophobic microstructures of titanium alloys, the structural design of the existing super-hydrophobic surface of titanium alloys is still lacking in terms of retaining air and reducing the contact area. Therefore, the present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure and a preparation method thereof with concave truncated cones and blind holes, designs a microstructure with periodic arrangement of concave truncated cones and blind holes, derives a numerical equation, realizes the controllable design of the theoretical value of the contact angle, and completes the processing of the microstructure by etching the titanium alloy surface through femtosecond laser, and reduces the surface energy by chemical fluorination, thereby realizing the preparation of the low-adhesion super-hydrophobic microstructure of titanium alloy. The present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure and a preparation method thereof with concave truncated cones and blind holes, provides a new design method and a low-cost preparation approach for low-adhesion titanium alloy super-hydrophobic surfaces, can be widely used in the fields of medical equipment, aerospace ice suppression, etc., and has important application value. Summary of the Invention

[0007] The present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof, designs a microstructure with periodic arrangement of concave truncated cones and blind holes, and derives and establishes a numerical equation based on the Cassie-Baxter infiltration model of super-hydrophobic theory, clarifies the microstructure characteristic parameters corresponding to a contact angle greater than 150°, and completes the design of the super-hydrophobic microstructure; selects a titanium alloy material and polishes it to 0.4~0.8 μm, performs femtosecond laser etching on the polished titanium alloy surface, and prepares a microstructure with periodic arrangement of concave truncated cones and blind holes; in order to eliminate the high adhesion characteristics of the titanium alloy super-hydrophobic microstructure, it is chemically fluorinated and dried at a constant temperature to obtain a titanium alloy super-hydrophobic microstructure with low adhesion characteristics. The technical solution adopted in the present invention is: A titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof, characterized by comprising the following steps: Step 1: Design a super-hydrophobic surface microstructure, which includes a micron-scale composite structure with periodic arrangement of concave truncated cones and blind holes; Step 2: Based on the Cassie-Baxter wetting model of superhydrophobic theory, a numerical equation is derived to establish the relationship between the microstructure of periodic arrangement of concave truncated cones and blind holes and the superhydrophobic function, i.e., the contact angle of a water droplet. The numerical equation is: , Where: θ T and θ c Represent the theoretical contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of water droplets on the titanium alloy surface θ c is 101°; r 1. r 2 、R、r3 are the radius of the top circle of the truncated cone, the radius of the pit circle, the radius of the bottom circle of the truncated cone, and the radius of the blind hole respectively; H, h, and h3 are the height of the truncated cone, the depth of the pit, and the depth of the blind hole respectively; n is the number of blind holes in the array; λ is the wetting coefficient, that is, the degree of wetting of the concave cone by the water droplet. When the water droplet floats on the top of the concave cone λ =0, when the water droplet completely soaks the concave cone λ =1; The numerical equation is used to determine the microstructure characteristic parameters corresponding to a water droplet contact angle greater than 150°, thereby completing the design of the superhydrophobic microstructure. Step 3: Select a titanium alloy material and polish it to a surface roughness of 0.4-0.8 μm, then clean it and place it in a constant temperature box at 40-50°C for 90 minutes to dry the polished titanium alloy surface; Step 4: femtosecond laser etching is performed on the polished and dried titanium alloy surface to prepare a microstructure with periodic arrangement of concave truncated cones and blind holes; Step 5: After femtosecond laser etching, the titanium alloy surface has high-adhesion superhydrophobic wetting properties, so chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The specific steps include: placing the titanium alloy superhydrophobic microstructure in a 1% to 5% by mass heptafluorosilane anhydrous ethanol solution for 3 to 4 hours, and drying it at a constant temperature of 80 to 90°C for 30 to 40 minutes to obtain a titanium alloy superhydrophobic surface with low adhesion properties.

[0008] Step 1 specifically includes: (1) Design a super-hydrophobic structure with periodic arrangement of concave truncated cones and blind holes, in which the concave truncated cones, blind holes, and substrate are an integrated structure; (2) When water droplets infiltrate the designed superhydrophobic microstructure, the superhydrophobic microstructure with periodic arrangement of concave truncated cones and blind holes can effectively retain air, form an air film layer, reduce the contact area, and achieve superhydrophobic function.

[0009] Step 2 specifically includes: (1) The designed concave cone and blind hole have micron-level structural characteristic parameters, among which the radius of the concave circle is r 2 Designed to be 7~9 μm, depth h Designed to be 0.5~1.5 μm; the radius of the bottom circle of the cone R Designed to be 16~20 μm, top circle radius r 1 Designed to be 8~10μm, the height of the frustum H 40~45 μm; blind hole radius r 3 Designed to be 1~2 μm, depth h 3 designed to be 2~4 μm; (2) The characteristic parameters of the microstructure of the periodic arrangement of concave truncated cones and blind holes are introduced into the numerical equation to calculate the theoretical value of the water droplet contact angle. The super-hydrophobic function is judged based on whether the contact angle is greater than 153°, thereby realizing the controllable design of the super-hydrophobic surface and clarifying the characteristic parameters of the super-hydrophobic microstructure.

[0010] Step 3 specifically includes: (1) Titanium alloy was selected as the matrix material of the superhydrophobic microstructure and cut into titanium alloy samples with a length × width of 2 cm × 2 cm; (2) Use a polishing machine to polish the surface of the titanium alloy sample to a surface roughness of 0.4~0.8 μm; (3) The polished titanium alloy sample was placed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. After cleaning, it was placed in a constant temperature box at 40~50℃ for 90 minutes to dry the cleaned titanium alloy sample.

[0011] Step 4 specifically includes: (1) Place the polished and dried titanium alloy sample on the three-dimensional motion platform of the femtosecond laser system, adjust the laser focus to the surface of the titanium alloy sample, and determine the laser scanning path based on the superhydrophobic microstructure characteristic parameters determined in step 2; (2) Set the femtosecond laser processing parameters: average power 10 W, beam radius 5 μm, pulse width 800 fs, laser frequency 300 kHz; (3) The processing of super-hydrophobic microstructures with periodic arrangement of concave truncated cones and blind holes can be completed by only a single femtosecond laser etching on the surface of the titanium alloy sample.

[0012] Step 5 specifically includes: (1) The titanium alloy surface after femtosecond laser etching has high adhesion and superhydrophobic wetting properties. Therefore, chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The titanium alloy sample after femtosecond laser etching is placed in a beaker, and a 1% to 5% by mass solution of heptafluorosilane in anhydrous ethanol is added. The beaker is sealed to prevent the solution from volatilizing and placed in a cool environment for 3 to 4 hours. (2) The titanium alloy sample after chemical fluorination treatment was placed in a constant temperature box at 80~90℃ and kept warm for 30~40 min to prepare a low-adhesion superhydrophobic microstructure of titanium alloy.

[0013] The present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method, designs a microstructure with periodic arrangement of concave truncated cones and blind holes, derives and establishes a numerical equation based on the Cassie-Baxter infiltration model of super-hydrophobic theory, clarifies the characteristic parameters of the microstructure, and realizes the controllable design of the super-hydrophobic microstructure; fully utilizes the advantages of high precision, controllability, flexibility and efficiency of femtosecond laser to complete the processing of the periodic arrangement of concave truncated cones and blind holes on the surface of the titanium alloy, uses 1% to 5% by mass of heptafluorosilane anhydrous ethanol solution to reduce the surface energy of the titanium alloy sample, and realizes the preparation of the titanium alloy low-adhesion super-hydrophobic microstructure, which has important application value in the fields of medical equipment, aerospace ice suppression, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 A schematic diagram of the overall structure of the present invention; Figure 2 Schematic diagram of the concave frustum and blind hole of the present invention; Figure 3 Schematic diagram of the femtosecond laser processing, scanning path and fluorination treatment of the present invention; Figure 4 Schematic diagram of a scanning electron microscope of a femtosecond laser-induced titanium alloy sample of the present invention; Figure 5 Schematic diagram of three-dimensional white light induced by femtosecond laser in a titanium alloy sample of the present invention; Figure 6 Schematic diagram of contact angle and rolling angle testing of titanium alloy samples of the present invention; Figure 7 An image showing the low adhesion property test process of the titanium alloy sample surface of the present invention; Figure 8 Design and preparation flow chart of the present invention.

[0015] In the figure: 1, concave truncated cone; 1-1, pit; 1-2, truncated cone; 2, blind hole; 3, titanium alloy substrate. DETAILED DESCRIPTION

[0016] The following is a detailed description of a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof, in conjunction with the embodiments and the accompanying drawings.

[0017] The present invention discloses a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof. A micro-nano composite structure with periodic arrangement of concave truncated cones and blind holes is designed. Based on the Cassie-Baxter infiltration model of super-hydrophobic theory, a numerical relationship between the microstructural characteristics of periodic arrangement of concave truncated cones and blind holes and the super-hydrophobic function, i.e., the contact angle of water droplets, is derived and established; the characteristic microstructural parameters of periodic arrangement of concave truncated cones and blind holes corresponding to a water droplet contact angle greater than 150° are clearly calculated. A titanium alloy material is selected for polishing treatment, and the super-hydrophobic microstructure designed by femtosecond laser etching is subjected to chemical fluorination treatment and constant temperature drying to eliminate the high adhesion characteristics of the titanium alloy super-hydrophobic microstructure. Thus, a titanium alloy super-hydrophobic microstructure with low adhesion characteristics is obtained.

[0018] The present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof, which specifically includes the following steps.

[0019] 1. Design a super-hydrophobic surface microstructure, i.e., a micron-scale composite structure composed of periodic arrangements of concave truncated cones and blind holes, specifically including: (1) Design a super-hydrophobic structure with periodic arrangement of concave truncated cones and blind holes, in which the concave truncated cones, blind holes and substrate are an integrated structure, such as Figure 1 As shown; (2) When water droplets infiltrate the designed superhydrophobic microstructure, the superhydrophobic microstructure with periodic arrangement of concave truncated cones and blind holes can effectively retain air, form an air film layer, reduce the contact area, and achieve superhydrophobic function.

[0020] 2. Based on the Cassie-Baxter wetting model of superhydrophobicity theory, a numerical equation was derived to establish the relationship between the microstructure of periodic arrangement of concave truncated cones and blind holes and the superhydrophobic function, namely the water droplet contact angle. The characteristic parameters of the microstructure corresponding to a water droplet contact angle greater than 153° were determined, and the superhydrophobic microstructure design was completed. The specific steps include the following: (1) The designed concave cone and blind hole have micron-level structural characteristic parameters, among which the radius of the concave circle is r 2 Designed to be 7~9 μm, depth h Designed to be 0.5~1.5 μm; the radius of the bottom circle of the cone R Designed to be 16~20 μm, top circle radius r 1 Designed to be 8~10μm, the height of the frustum H 40~45 μm; blind hole radius r 3 Designed to be 1~2 μm, depth h 3 is designed to be 2~4 μm, such as Figure 2 As shown; (2) Based on the Cassie-Baxter wetting model of superhydrophobic theory, a numerical equation is derived to establish the relationship between the microstructural characteristics of the periodic arrangement of concave truncated cones and blind holes and the superhydrophobic function, namely the contact angle of the water droplet. The Cassie-Baxter wetting model assumes that when a droplet infiltrates a solid surface, air can be retained in the microstructure of the solid surface. Therefore, the contact surface consists of three parts: the droplet, air, and the solid surface microstructure. Based on this, the Cassie-Baxter equation is proposed: (1) , Where, θ T is the contact angle, θ c is the intrinsic contact angle, f s1 is the ratio of the actual wetted solid area of ​​the droplet to the apparent geometric contact area. f r Indicates the roughness coefficient, that is, the non-smoothness of the surface. Figure 1 、 Figure 2 As shown in the figure, the designed super-hydrophobic microstructure is composed of periodically arranged concave truncated cones and blind holes, and the projected area of ​​the unit microstructure is S P It can be calculated by formula (2): (2), The actual surface area S generated by the unit microstructure S It is composed of the concave truncated cone pit 1-1, truncated cone 1-2, blind hole 2, and base 3, and is calculated by the following formula: (3), Where, r 1 、 r 2 、R、r 3 are respectively the top circle radius of the cone 1-2, the radius of the pit 1-1 circle, the bottom circle radius of the cone 1-2, and the radius of the blind hole 2; H 、 h 、 h 3 are the height of the cone 1-2, the depth of the pit 1-1, and the depth of the blind hole 2; n is the number of array blind holes 2; According to this roughness coefficient f r It can be expressed as: (4), When water droplets infiltrate the designed super-hydrophobic microstructure with periodic arrangement of concave truncated cones and blind holes, they produce different degrees of infiltration on the concave truncated cones 1, so the infiltration coefficient is introduced. λ; At this time, the water droplet infiltrates the concave truncated cone, so the ratio of the area of ​​the concave truncated cone 1 actually infiltrated by the water droplet to the apparent geometric contact area is f s1 It can be obtained by formula (5): (5), Where: f s1 It represents the ratio of the actual solid area wetted by the droplet to the apparent geometric contact area; λ represents the wetting coefficient; Substituting formula (4) and formula (5) into formula (1), the numerical relationship between the designed micro-nano composite structure characteristics and the superhydrophobic function, i.e., the water droplet contact angle, can be obtained as follows: (6), Where: θ T and θ c Represent the theoretical contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of water droplets on the titanium alloy surface θ c is 101°; (3) Substitute the characteristic parameters of the microstructure of the periodic arrangement of concave truncated cones and blind holes into the numerical equation to calculate the theoretical value of the water drop contact angle. The super-hydrophobic function is determined based on whether the contact angle is greater than 150°, and the characteristic parameters of the super-hydrophobic microstructure are clarified. In the embodiment, the characteristic parameters are set as: the radius of the concave pit circle r 2 Designed to be 8 μm deep h Designed to be 1 μm; the radius of the bottom circle of the cone R Designed to be 18 μm, the top circle radius r 1 is designed to be 9 μm, with a cone height of H 40 μm; blind hole radius r 3 Designed to 2μm, depth h 3 designed to 3 μm, number of blind holes n is 181, and the wetting coefficient is λ =0.9. Substitute the above parameters into formula (6) to calculate the contact angle of the designed superhydrophobic surface θ T =154.16°, indicating good superhydrophobicity.

[0021] 3. Select titanium alloy material for polishing to make the surface roughness reach 0.4~0.8 μm, then clean and place it in a constant temperature box at 40~50℃ for 90 minutes to dry the polished titanium alloy surface. Specifically include: (1) Ti6Al4V alloy was selected as the superhydrophobic microstructure matrix material from titanium alloy materials and cut into titanium alloy samples with a length × width of 2 cm × 2 cm; (2) Use a polishing machine to polish the surface of the titanium alloy sample to a surface roughness of 0.4~0.8 μm; (3) The polished titanium alloy sample was placed in anhydrous ethanol and ultrasonically cleaned for 5 minutes. After cleaning, it was placed in a constant temperature box at 40~50℃ for 90 minutes to dry the cleaned titanium alloy sample.

[0022] 4. Perform femtosecond laser etching on the polished and dried titanium alloy surface to produce a microstructure with periodic arrangement of concave truncated cones and blind holes, specifically including: (1) The polished and dried titanium alloy sample was placed on the three-dimensional motion platform of a femtosecond laser (YLC-03, Changzhou Company, China) system. The laser focus was adjusted to the surface of the titanium alloy sample. The laser scanning path was determined by the characteristic parameters of the superhydrophobic microstructure determined in step 2. (2) Set the femtosecond laser processing parameters: average power 10 W, beam radius 5 μm, pulse width 800 fs, laser frequency 300 kHz; (3) The processing of super-hydrophobic microstructures with periodic arrangement of concave truncated cones and blind holes can be completed by only a single femtosecond laser etching on the surface of the titanium alloy sample.

[0023] 5. Since the titanium alloy surface has high adhesion and super-hydrophobic wetting properties after femtosecond laser etching, chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The specific steps include: (1) The titanium alloy surface after femtosecond laser etching has high adhesion and superhydrophobic wetting properties. Therefore, chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The titanium alloy sample after femtosecond laser etching is placed in a beaker, and a 1% by mass solution of heptafluorosilane (perfluorodecyltriethoxysilane) in anhydrous ethanol is added. The beaker is sealed to prevent the solution from volatilizing and placed in a cool environment for 3 h. (2) The titanium alloy sample after chemical fluorination treatment was placed in a constant temperature box at 80℃ and kept warm for 40 minutes to prepare a low-adhesion super-hydrophobic microstructure of titanium alloy. The process is as follows: Figure 3 shown.

[0024] In order to verify the superiority and feasibility of the low-adhesion super-hydrophobic microstructure of titanium alloy with concave cones and blind holes and the preparation method of the present invention, the wettability characterization test of the super-hydrophobic surface of the titanium alloy was carried out, and the contact angle and rolling angle of the water droplet on the super-hydrophobic surface were obtained by multiple measurements; the morphology and three-dimensional structure of the super-hydrophobic surface of the titanium alloy were obtained; and the adhesion of the super-hydrophobic surface of the titanium alloy was characterized and tested, which specifically included the following four aspects.

[0025] (1) The super-hydrophobic surface morphology of the titanium alloy was characterized by scanning electron microscopy (SEM, SU 8600, Carl Zeiss AG, Germany). Figure 4 As shown in the scanning electron microscope images at different magnifications, it is clear that the periodically arranged concave truncated cones and blind hole structures obtained by single femtosecond laser etching and chemical fluorination treatment are clearly visible, and a large number of nano-scale particles are distributed on the surface of the processed super-hydrophobic microstructure.

[0026] (2) The three-dimensional morphology of the super-hydrophobic surface of the titanium alloy was characterized by scanning white light interferometry (SWLI, SuperViewW3, Chotest Corp, China). Figure 5 As shown in the 3D white light interferogram, the 3D structural dimensions of the periodically arranged concave truncated cones and blind holes obtained by single femtosecond laser etching and chemical fluorination treatment can be clearly seen. The microstructure obtained by femtosecond laser etching meets the design expectations within the error and accuracy range.

[0027] (3) The contact angle and rolling angle of the droplet on the super-hydrophobic surface of the titanium alloy were measured using a contact angle meter (SL-200KS, Solon, USA). Figure 6 The specific testing method involves measuring the contact angle of a water droplet on a super-hydrophobic titanium alloy surface using a contact angle meter. A titanium alloy sample was placed on a measuring platform, and a 5μL water droplet was dropped onto the super-hydrophobic titanium alloy surface. The measured contact angle was 153.81±1.4°, which is consistent with the contact angle calculated using the numerical equation. The angle α at which the water droplet critically rolls on the super-hydrophobic titanium alloy surface was recorded as 9.73°, using a motor to control the platform's tilt angle.

[0028] (4) The low adhesion properties of the super hydrophobic surface of the titanium alloy are tested, such as Figure 7 The specific test method is as follows: a 5μL water droplet is controlled to contact, squeeze, stretch, and separate from the prepared titanium alloy super-hydrophobic surface. During the entire operation, no water stains remain on the titanium alloy super-hydrophobic surface, and the volume of the water droplet does not change.

[0029] In summary, the present invention provides a titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof. The overall operation process is as follows: Figure 8 The present invention provides a new design method and low-cost preparation approach for low-adhesion titanium alloy super-hydrophobic microstructures, which can be widely used in medical devices, aerospace ice suppression and other fields.

Claims

1. A titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and a preparation method thereof, characterized in that The design steps include: Step 1, designing a super-hydrophobic surface microstructure, namely, a micron-scale composite structure composed of concave truncated cones and blind holes arranged periodically; Step 2, based on the Cassie-Baxter wetting model of superhydrophobic theory, a numerical equation is derived between the microstructure of periodic arrangement of concave truncated cones and blind holes and the superhydrophobic function, i.e., the contact angle of a water droplet. The numerical equation is:

2. In the formula: θ T and θ c They represent the theoretical contact angle and the intrinsic contact angle, respectively. The intrinsic contact angle of a water drop on the titanium alloy surface θ c is 101°; r 1. r 2 、R、r 3 are the radius of the top circle of the truncated cone, the radius of the pit circle, the radius of the bottom circle of the truncated cone, and the radius of the blind hole; H, h, and h3 are the height of the truncated cone, the depth of the pit, and the depth of the blind hole respectively; n is the number of blind holes in the array; λ is the wetting coefficient, that is, the degree of wetting of the concave cone by the water drop. When the water drop floats on the top of the concave cone λ =0, when the water droplet completely wets the concave cone λ =1; The numerical equation is used to determine the microstructure characteristic parameters corresponding to a water drop contact angle greater than 150°, thereby completing the design of a superhydrophobic microstructure. Step 3, select a titanium alloy material for polishing to make the surface roughness reach 0.4-0.8 μm, then clean and place it in a constant temperature box at 40-50° C. and maintain for 90 min to dry the polished titanium alloy surface; Step 4, performing femtosecond laser etching on the polished and dried titanium alloy surface to prepare a microstructure with periodic arrangement of concave truncated cones and blind holes; Step 5: After femtosecond laser etching, the titanium alloy surface has high adhesion and super hydrophobic wetting properties, so chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The specific steps include: The titanium alloy super-hydrophobic microstructure was placed in a 1%~5% by mass ratio heptafluorosilane anhydrous ethanol solution for 3~4 h and dried at a constant temperature of 80~90℃ for 30~40 min to obtain a titanium alloy super-hydrophobic surface with low adhesion properties.

3. The titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and the preparation method thereof according to claim 1, characterized in that: Step 1 specifically includes: (1) Designing a super-hydrophobic structure with periodic arrangement of concave truncated cones and blind holes, wherein the concave truncated cones, blind holes, and substrate are an integrated structure; (2) When water droplets infiltrate the designed superhydrophobic microstructure, the superhydrophobic microstructure with periodic arrangement of concave cones and blind holes can effectively retain air, form an air film layer, reduce the contact area, and achieve superhydrophobic function.

4. The titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and the preparation method thereof according to claim 1, characterized in that: Step 2 specifically includes: (1) The designed concave cone and blind hole have micron-scale structural characteristic parameters, among which the radius of the concave circle r 2 Designed to be 7~9 μm, depth h Designed to be 0.5~1.5 μm; the radius of the bottom circle of the truncated cone R Designed to be 16~20 μm, top circle radius r 1 Designed to be 8~10 μm, the height of the frustum H 40~45 μm; blind hole radius r 3 Designed to be 1~2 μm, depth h 3 Designed to be 2~4 μm; (2) The microstructural characteristic parameters of the periodic arrangement of concave cones and blind holes are substituted into the numerical equation to calculate the theoretical value of the water droplet contact angle. The super-hydrophobic function is determined based on whether the contact angle is greater than 150°. This enables the controllable design of the super-hydrophobic surface and clarifies the characteristic parameters of the super-hydrophobic microstructure.

5. The titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and the preparation method thereof according to claim 1, characterized in that: Step 3 specifically includes: (1) Select titanium alloy as the base material of the superhydrophobic microstructure and cut it into titanium alloy samples with a length × width of 2 cm × 2 cm; (2) Use a polishing machine to polish the surface of the titanium alloy sample to a surface roughness of 0.4-0.8 μm; (3) The polished titanium alloy sample was placed in anhydrous ethanol and ultrasonically cleaned for 5 min. After cleaning, it was placed in a constant temperature box at 40-50 °C for 90 min to dry the cleaned titanium alloy sample.

6. The titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and the preparation method thereof according to claim 1, characterized in that: Step 4 specifically includes: (1) Place the polished and dried titanium alloy sample on the three-dimensional motion platform of the femtosecond laser system, adjust the laser focus to the surface of the titanium alloy sample, and determine the laser scanning path according to the superhydrophobic microstructure characteristic parameters determined in step 2; (2) Set the femtosecond laser processing parameters: average power 10 W, beam radius 5 μm, pulse width 800 fs, laser frequency 300 kHz; (3) The processing of super-hydrophobic microstructures with periodic arrangement of concave truncated cones and blind holes can be completed by only a single femtosecond laser etching on the surface of the titanium alloy sample.

7. The titanium alloy low-adhesion super-hydrophobic microstructure with concave truncated cones and blind holes and the preparation method thereof according to claim 1, characterized in that: Step 5 specifically includes: (1) The titanium alloy surface after femtosecond laser etching has high adhesion and superhydrophobic wetting properties. Therefore, chemical fluorination treatment is performed to reduce the surface energy of the titanium alloy surface. The titanium alloy sample after femtosecond laser etching is placed in a beaker, and a 1% to 5% mass ratio of heptafluorosilane anhydrous ethanol solution is added. The beaker is sealed to prevent the solution from volatilizing and placed in a cool environment for 3 to 4 h. (2) The titanium alloy sample after chemical fluorination treatment was placed in a constant temperature box at 80~90℃ and kept warm for 30~40 min to prepare a titanium alloy low adhesion superhydrophobic microstructure.